A Snapshot of Health Equity in Papua New Guinea : An Analysis of the 2010 Household Income and Expenditure Survey - Irava, Wayne; Barker, Katie; Somanathan, Aparnaa; Hou, Xiaohui (World Bank, Washington, DC, 2015)
This paper highlights challenges that the government of Papua New Guinea faces in delivering equitable health care. It analyses findings from the 2010 household survey, including sickness reporting, health service utilization and out of pocket expenditure, concluding that the poorest quintile is most vulnerable to illness, yet has the lowest utilization rates of healthcare facilities. The lack of healthcare workers and the distance to facilities are among the most dominant reasons cited for not utilizing healthcare facilities in the poorest quintile while out-of-pocket payments have minimal catastrophic impact, yet have still been found to be a barrier to utilization. The paper also sets out policy implications of these findings, including the need for the government to focus on, and prioritize, strengthening the health services delivery to achieve universal health coverage.